Pengaruh Variasi Waktu Operasi Mesin Terhadap Perubahan Nilai Viskositas Dan Total Acid Number Untuk Pelumas Gearbox - Putra, Dika Septayama; Ariyanto, Ariyanto; Feriadi, Indra (Jurnal Inovasi Teknologi Terapan, 2023)
Lubricating is one of the methods to prevent temperature rise and wear due to friction among gearbox components. The lubricant quality is an essential factor in ensuring lubricant functions optimally. Long-term use of the machine changes lubricant quality, which can be measured by viscosity parameters and Total Acid Number (TAN). This research aims to determine the effect of machine operating time on viscosity and TAN lubricant changes of milling machine gearbox heads (Headstock) used for educational purposes. The study used a quantitative research method in which data was collected using statistical data analysis tools and selecting a random sampling. Forty samples of Shell Tellus 46 lubricant were taken every 5 hours for 200 operation hours with an operating temperature of 27.5-44.4°C and 300 rpm speed. Viscosity testing uses Visgage and Fluidscan to check TAN. Data analysis using a simple linear regression analysis method with the statistical software Minitab 21.3. The results showed that operating time had a significant effect on: 1) a 95% change in viscosity value with 3.67 cSt (7.39%) decline or 0.018776 cSt per operation hour; 2) 99.34% change in TAN value with 0.27 mg KOH/g (16.56%) increase or 0.001297 mg KOH/g per operation hour.